Paradigma Pendidikan Holistik dalam Al-Qur'an: Analisis Tafsir Tematik tentang Integrasi Tarbiyah, Ta'lim, dan Ta'dib - St. Dewi Nurul Fitrizki Dewi; Hasyim Haddade; Hamka Ilyas; Muh Nur Fithri Muh Nur Fithri (STAI YAPIS Takalar, 2026)
The dichotomy between education oriented toward knowledge acquisition and character formation highlights the need to reconstruct a more holistic paradigm of Islamic education. This study aims to examine the holistic educational paradigm in the Qur'an through the integration of the concepts of tarbiyah, ta'lim, and ta'dib using a thematic (maw??‘?) Qur'anic exegesis approach. This research employs a library research design, with the Qur'anic verses related to education serving as the primary data source, complemented by classical and contemporary Qur'anic commentaries as well as Islamic education literature as secondary sources. The analysis was conducted through several stages, including the identification of relevant verses, thematic classification, linguistic and contextual analysis, synthesis of interrelated meanings, and interpretation by relating the findings to contemporary educational theories. The findings reveal that the Qur'anic educational paradigm is inherently holistic, integrating tarbiyah as the process of nurturing human potential, ta'lim as the development of knowledge, and ta'dib as the cultivation of ethical conduct and civilized character. These three concepts collectively establish a comprehensive educational paradigm that balances intellectual, spiritual, moral, and social dimensions, making it highly relevant as a foundational framework for the development of contemporary Islamic education aimed at nurturing knowledgeable, morally upright, and civilized individuals.